Death and the mother from Dickens to Freud : Victorian fiction and the anxiety of origins - Dever, Carolyn (Cambridge University Press, 1998)
The cultural ideal of motherhood in Victorian Britain seems to be undermined by Victorian novels, which almost always represent mothers as incapacitated, abandoning or dead. Carolyn Dever argues that the phenomenon of the dead or missing mother in Victorian narrative is central to the construction of the good mother as a cultural ideal. Maternal loss is the prerequisite for Victorian representations of domestic life, a fact which has especially complex implications for women. When Freud constructs psychoanalytical models of family, gender and desire, he too assumes that domesticity begins with the death of the mother. Analysing texts by Dickens, Collins, Eliot, Darwin and Woolf, as well as Freud, Klein and Winnicott, Dever argues that fictional and theoretical narratives alike use maternal absence to articulate concerns about gender and representation. Psychoanalysis has long been used to analyse Victorian fiction; Dever contends that Victorian fiction has much to teach us about psychoanalysis.
Keywords: English fiction -- 19th century -- History and criticism.; Mothers in literature.; Psychoanalysis and literature -- Great Britain -- History -- 19th century.; Literature and society -- Great Britain -- History -- 19th century.; Women and literature -- Great Britain -- History -- 19th century.; Psychological fiction, English -- History and criticism.; Maternal deprivation in literature.; Motherhood in literature.; Sex role in literature.; Death in literature.; Roman anglais -- 19e siècle -- Histoire et critique.; Mères dans la littérature.; Psychanalyse et littérature -- Grande-Bretagne -- Histoire -- 19e siècle.; Littérature et société -- Grande-Bretagne -- Histoire -- 19e siècle.; Femmes et littérature -- Grande-Bretagne -- Histoire -- 19e siècle.; Carence maternelle dans la littérature.; Maternité dans la littérature.; Rôle selon le sexe dans la littérature.; Mort dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Death in literature; English fiction; Literature and society; Maternal deprivation in literature; Motherhood in literature; Mothers in literature; Psychoanalysis and literature; Psychological fiction, English; Sex role in literature; Women and literature; Great Britain; Victoriaanse tijd.; Fictie.; Dood.; Moeders.; English.; Languages & Literatures.; English Literature.; 1800-1899; Criticism, interpretation, etc.; History